Training to enhance psychiatrist communication with patients with psychosis (TEMPO): cluster randomised controlled trial. (December 2016) - McCabe, Rose; John, Paula; Dooley, Jemima; Healey, Patrick; Cushing, Annie; Kingdon, David; Bremner, Stephen; Priebe, Stefan
Abstract : Background: A better therapeutic relationship predicts better outcomes. However, there is no trial-based evidence on how to improve therapeutic relationships in psychosis. Aims: To test the effectiveness of communication training for psychiatrists on improving shared understanding and the therapeutic relationship (trial registration: ISRCTN94846422). Method: In a cluster randomised controlled trial in the UK, 21 psychiatrists were randomised. Ninety-seven (51% of those approached) out-patients with schizophrenia/schizoaffective disorder were recruited, and 64 (66% of the sample recruited at baseline) were followed up after 5 months. The intervention group received four group and one individualised session. The primary outcome, rated blind, was psychiatrist effort in establishing shared understanding (self-repair). Secondary outcome was the therapeutic relationship. Results: Psychiatrists receiving the intervention used 44% more self-repair than the control group (adjusted difference in means 6.4, 95% CI 1.46–11.33, P <0.011, a large effect) adjusting for baseline self-repair. Psychiatrists rated the therapeutic relationship more positively (adjusted difference in means 0.20, 95% CI 0.03–0.37, P = 0.022, a medium effect), as did patients (adjusted difference in means 0.21, 95% CI 0.01–0.41, P = 0.043, a medium effect). Conclusions: Shared understanding can be successfully targeted in training and improves relationships in treating psychosis.